Optimalisasi Senam Diabetes dalam Meningkatkan Sensitivitas Kaki pada Pasien Diabetes Mellitus Tipe 2 melalui Program Pengabdian Masyarakat - Ismail Ismail (Jurnal Inovasi Pengabdian Masyarakat Celebes, 2026)
Type 2 diabetes mellitus is a chronic metabolic disease that often causes complications such as peripheral neuropathy, characterized by decreased foot sensitivity. This condition increases the risk of diabetic foot ulcers. Physical activities such as diabetes exercises have the potential to improve peripheral circulation and nerve function. This study aims to analyze the optimization of diabetes exercises in improving foot sensitivity in patients with type 2 diabetes mellitus through a community service program. This study used an observational analytical design with a cross-sectional approach. The community service activities were carried out from October–November 2025 in the Biringkanaya area, Makassar City. Data were obtained from the Sudiang Raya Community Health Center database. The study sample consisted of 45 respondents selected using purposive sampling. Data analysis used the Chi-square test,logistic regression, and ROC analysis. Respondents who regularly participated in diabetes exercises showed a higher proportion of normal foot sensitivity. Statistical analysis showed a significant relationship between diabetes exercises and foot sensitivity (p < 0.05). The AUC value of 0.70 indicates sufficient predictive ability. Diabetes exercises have the potential to improve foot sensitivity in patients with type 2 diabetes mellitus.